Bio-hydrogen production based on catalytic reforming of volatiles generated by cellulose pyrolysis: an integrated process for ZnO reduction and zinc nanostructures fabrication - Maciel, Adriana V.; Job, Aldo Eloizo [UNESP]; Mussel, Wagner da Nova; Brito, Walter; Pasa, Vanya Marcia Duarte (Elsevier, 2011)
The paper presents a process of cellulose thermal degradation with bio-hydrogen generation and zinc nanostructures synthesis. Production of zinc nanowires and zinc nanoflowers was performed by a novel processes based on cellulose pyrolysis, volatiles reforming and direct reduction of ZnO. The bio-hydrogen generated in situ promoted the ZnO reduction with Zn nanostructures formation by vapor–solid (VS) route. The cellulose and cellulose/ZnO samples were characterized by thermal analyses (TG/DTG/DTA) and the gases evolved were analyzed by FTIR spectroscopy (TG/FTIR). The hydrogen was detected by TPR (Temperature Programmed Reaction) tests. The results showed that in the presence of ZnO the cellulose thermal degradation produced larger amounts of H2 when compared to pure cellulose. The process was also carried out in a tubular furnace with N2 atmosphere, at temperatures up to 900 °C, and different heating rates. The nanostructures growth was catalyst-free, without pressure reduction, at temperatures lower than those required in the carbothermal reduction of ZnO with fossil carbon. The nanostructures were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS) and transmission electron microscopy (TEM). The optical properties were investigated by photoluminescence (PL). One mechanism was presented in an attempt to explain the synthesis of zinc nanostructures that are crystalline, were obtained without significant re-oxidation and whose morphologies are dependent on the heating rates of the process. This route presents a potential use as an industrial process taking into account the simple operational conditions, the low costs of cellulose and the importance of bio-hydrogen and nanostructured zinc.
Keywords: Cellulose pyrolysis; Catalytic reforming; Bio-hydrogen; Zinc nanostructures; TG-FTIR spectroscopy